Resonance Raman Probes for Organelle-Specific Labeling in Live Cells - Kuzmin, Andrey N.; Pliss, Artem; Lim, Chang-Keun; Heo, Jeongyun; Kim, Sehoon; Rzhevskii, Alexander; Gu, Bobo; Yong, Ken-Tye; Wen, Shangchun; Prasad, Paras N. (NATURE PUBLISHING GROUP, 2016)
Raman microspectroscopy provides for high-resolution non-invasive molecular analysis of biological samples and has a breakthrough potential for dissection of cellular molecular composition at a single organelle level. However, the potential of Raman microspectroscopy can be fully realized only when novel types of molecular probes distinguishable in the Raman spectroscopy modality are developed for labeling of specific cellular domains to guide spectrochemical spatial imaging. Here we report on the design of a next generation Raman probe, based on BlackBerry Quencher 650 compound, which provides unprecedentedly high signal intensity through the Resonance Raman (RR) enhancement mechanism. Remarkably, RR enhancement occurs with low-toxic red light, which is close to maximum transparency in the biological optical window. The utility of proposed RR probes was validated for targeting lysosomes in live cultured cells, which enabled identification and subsequent monitoring of dynamic changes in this organelle by Raman imaging.
Keywords: SPECTROSCOPY; MICROSCOPY; SERS; DNA; TRANSFORMATIONS; NUCLEOLI; PROTEOME